Pengaruh Rasio Likuiditas dan Solvabilitas Terhadap Profitabilitas dengan Penggunaan Teknologi Informasi Sebagai Variabel Moderasi - Arief Adhy Kurniawan; Sutarmin Sutarmin (JBIMA (Jurnal Bisnis dan Manajemen), 2016)
The problem in this research is about the uncertainty of achieving the company profitability, so management needs to minimize business risk by predicting variables that affect the profitability. The aims of this research was to determine the effect of liquidity ratios, solvency, the use of information technology to profitability, the influence of information technology in moderating variable between ratios of liquidity and solvency to profitability. Studied company is banking companies in the Indonesia stock exchange. The analytical method used is linear regression analysis with moderation. The results of this study can be concluded liquidity ratios significant positive effect on profitability, solvency does not affect the profitability, the use of information technology has no effect on profitability, use of information technology can moderate the relationship variables liquidity to profitability.